The Impact of Artificial Intelligence on Programmer Jobs: Threat or Opportunity? - Agustia Hananto; Nadya Susanti Hasibuan; Stevi Olivia; Tukino Tukino; Elfina Novalia (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2025)
The integration of artificial intelligence (AI) into software development has significantly reshaped the programming profession. This study investigates the dual impact of AI—particularly Generative AI tools such as ChatGPT and Codex—on programming jobs, examining both the potential threats and emerging opportunities. Using a Systematic Literature Review (SLR) approach, 18 peer-reviewed articles published within the last five years were analyzed. The findings reveal that while AI automates routine tasks such as code generation, debugging, and testing—raising concerns about the reduction of entry-level roles—it simultaneously enables programmers to assume more strategic functions in AI integration, system design, and ethical governance. Additionally, AI fosters inclusive programming environments by empowering non-experts through accessible development tools. The study emphasizes the need for continuous skill enhancement, human–AI collaboration, and policy support to ensure sustainable adaptation. This research contributes to a deeper understanding of AI's transformative influence on programming and proposes strategies for thriving in an AI-augmented digital workforce.